Electric field-induced phase transition and energy storage performance of highly-textured PbZrO3 antiferroelectric films with a deposition temperature dependence. Issue 15 (December 2018) - Nguyen, Minh D.; Rijnders, Guus
Abstract: Thin PbZrO3 (PZO) antiferroelectric films with (001)-preferred orientation were deposited on SrRuO3 /Ca2 Nb3 O10 -nanosheet/Si substrates using pulsed laser deposition. Variation of the deposition temperature was found to play a key role in the control of the microstructure and strongly influence the energy storage performance of the thin film. The critical phase switching field, where the aligned antiferroelectric (AFE) domains start to transform into the ferroelectric (FE) state, decreased with increasing temperature. On the other hand, the content of the FE phase in the AFE PZO thin films increased with increasing deposition temperature. A large recoverable energy-storage density of 16.8 J/cm 3 and high energy-storage efficiency of 69.2% under an electric field of 1000 kV/cm were achieved in the films deposited at 525 °C. This performance was due to the high forward switching field and backward switching field values and the low difference between these two fields. Moreover, the PZO thin films showed great charge-discharge cycling life with fatigue-free performance up to 10 10 cycles and good thermal stability from room temperature to 100 °C.